Heparanase Promotes Syndecan-1 Expression to Mediate Fibrillar Collagen and Mammographic Density in Human Breast Tissue Cultured ex vivo - Huang, Xuan; Reye, Gina; Momot, Konstantin I.; Blick, Tony; Lloyd, Thomas; Tilley, Wayne D.; Hickey, Theresa E.; Snell, Cameron E.; Okolicsanyi, Rachel K.; Haupt, Larisa M.; Ferro, Vito; Thompson, Erik W.; et al. (Frontiers in Cell and Developmental Biology, 2020)
Mammographic density (MD) is a strong and independent breast cancer (BC) risk factor and is increasingly associated with BC progression. We have previously shown in mice that high MD, characterized by the preponderance of a fibrous stroma, facilitates BC xenograft growth and metastasis. This stroma is rich in extracellular matrix (ECM) factors, including Heparan Sulfate proteoglycans (HSPGs), such as the BC-associated Syndecan-1 (SDC1). HSPGs tether growth factors, which are released by Heparanase (HPSE). MD is positively associated with estrogen exposure and estrogen has been implicated in the upregulation of HPSE, the activity of which promotes SDC expression. We describe a patient-derived explant (PDE) model of normal human (female) mammary tissue cultured ex vivo to investigate the role(s) of HPSE and SDC1 on MD as assessed by single-sided MRI. Relative HSPG gene and protein expression analyses in patient-paired high versus low MD tissues identified SDC1 and SDC4 as potential mediators of MD. Using the PDE model we demonstrate that HPSE promotes SDC1 expression and cleavage, rather than SDC4, leading to increased MD. In this model system, the SDC1 inhibitory peptide synstatin (SSTN), designed to decouple SDC1 / integrin alpha V beta 3-mediated parallel collagen alignment, reduced the abundance of fibrillar collagen as assessed by picrosirius red staining viewed under polarized light, and reduced MD. Our results reveal a potential role for HPSE in maintaining MD via its direct regulation of SDC1, which in turn physically tethers collagen into the aligned fibers that are characteristic of MD. We propose that inhibitors of HPSE and/or SDC1 may afford an opportunity to reduce MD in high BC risk individuals and reduce MD-associated BC progression in conjunction with established BC therapies.